Rutinitas Senam Hamil dengan Melahirkan Spontan - Ratna Dewi Puspita Sari; Sutarto Sutarto; Winda Trijayanthi Utama; Dian Pratiwi (Penerbit Goodwood, 2023)
Purpose: The length of labor can be caused by many factors, including inadequate contractions, fetal factors and birth canal factors. Factors that affect labor include: power, passage, passenger, psychic, and helper. Pregnancy exercise is an exercise to train the muscles so that they function optimally in normal delivery. The purpose of this study is to provide knowledge, benefits, and preparation for childbirth in pregnant women. Method: The method used in this study is a literature review using Publish or Perish (PoP) databases, Scopus, and Google Schooler. The purpose of using this method is to analyze the articles that have been obtained. Results: Exercise for pregnant women can reduce discomfort or anxiety during pregnancy and prepare physically and psychologically during the process of waiting to give birth. Sports that can be done by pregnant women during pregnancy are pregnancy exercise, pregnancy yoga, and other sports, of course, with assistance from health workers. Limitations: This article is only for analysis and does not carry out direct research. Contribution: With knowledge, preparation for childbirth and accompanied by the right health personnel, pregnant women will be able to give birth smoothly, safely and is expected to reduce the Maternal Mortality Rate and Infant Mortality Rate.